Forming of Informational Culture of Personality in Context of School Economic Education - L. B. Bakhtigulova (Tsentr nauchnykh i obrazovatelnykh proektov, 2018)
The review of G. E. Korolyova and M. G. Sergeyeva’s monograph “Information and communication technologies in economic education of high school students” reports that the book presents the scientific foundations for continuing economic education, including the genesis of economic thought in Russia, taking into account foreign experience in the use of information and communication technologies in school economics education. The interpretation of informatization of school economic education in modern conditions is positively estimated from the point of view of an assessment of opportunities and risks of informatization of school economic education and taking into account available experience of studying of economy in high school.